Lenin im Jahre 1917 - Reisberg, Arnold 1904-1980 (Dietz, 1967)
Biographie ; Völkerbund ; Februarrevolution ; Exil ; Deutschlandreise ; Bolschewisten ; Sowjets ; Große Sozialistische Oktoberrevolution ; Sozialismus